The defect chemistry of non-stoichiometric PuO2±x. Issue 8 (18th February 2021) - Neilson, William D.; Pegg, James T.; Steele, Helen; Murphy, Samuel T.
Abstract : An increased knowledge of the chemistry of PuO2 is imperative for the design of procedures to store, dispose, or make use of PuO2 . Abstract : An increased knowledge of the chemistry of PuO2 is imperative for the design of procedures to store, dispose, or make use of PuO2 . In this work, point defect concentrations in PuO2 are determined by combining density functional theory (DFT) defect energies and empirical potential calculations of vibrational entropies. The obtained defect concentrations are expressed as a function of temperature and oxygen partial pressure and used to calculate non-stoichiometry in PuO2± x . The results show that the defect chemistry of PuO2 is dominated by oxygen vacancies and interstitials. Hypo-stoichiometric PuO2− x is accommodated by both the uncharged oxygen vacancy and positively charged oxygen vacancy at small values of x, with increasingly dominant with increasing x . The negatively charged oxygen interstitial (O2−i) is found to accommodate hyper-stoichiometry (PuO2+ x ), but reluctance to form hyper-stoichiometric PuO2+ x is observed, with oxygen interstitials present only in very low concentrations irrespective of conditions. The small degree of hyper-stoichiometry found is favoured by low temperatures.